Development of Lecture Attendance System for Staff Performance Rating in a Tertiary Institution using Fingerprint Technology - Taiwo Gabriel OMOMULE; Dr. Alaba Olu AKINGBESOTE; Odunayo Olayinka BAYODE; Gabriel Omojokun AJU (International Journal of Engineering and Management Research, 2019)
Managing time attendance of staff in organizations has proven to be a challenging endeavor. Manual methods have been proposed in capturing employees’ attendance but there are inadequacies in measuring the performance of employees. This paper aims at promoting staff efficiency at work by developing a secure attendance management system for use in tertiary institutions via two subsystems; Fingerprint biometrics as a method of identification and authentication and Question-Answering module for staff performance rating. The system uses staff fingerprints stored in the database upon registration for carrying out the process of attendance and validate staff lectures’ requirements. It is accentuated by creating a question-answering module that allows students to answer some questions on each available and registered staff, hence, giving a more concentrated content about staff’s activities within the school. The evaluation was carried out based on the matching efficiency and attendance accuracy of the proposed system. The proposed system performed excellently with 98.51% attendance accuracy based on the high successful staff identification recorded. Hence, staff performance rating was generated, thereby creating an avenue for determining promotion grounds.